2019
DOI: 10.3390/brainsci10010002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Low Intracranial Pressure Headaches—What Is Known?

Abstract: Headaches attributed to low cerebrospinal fluid (CSF) pressure are described as orthostatic headaches caused by spontaneous or secondary low CSF pressure or CSF leakages. Regardless of the cause, CFS leaks may lead to intracranial hypotension (IH) and influence cerebral blood flow (CBF). When CSF volume decreases, a compensative increase in intracranial blood volume and cerebral vasodilatation occurs. Sinking of the brain and traction on pain-sensitive structures are thought to be the causes of orthostatic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Any change in intracranial pressure caused by intracranial hypotension may influence the cerebral blood flow. Most studies revealed the intracranial vessel dilatation, a cerebral blood flow increase, a flow velocity decrease, and cerebral venous thrombosis whereas some studies showed intracranial hypotension associated with vasoconstrictions and flow velocity increases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any change in intracranial pressure caused by intracranial hypotension may influence the cerebral blood flow. Most studies revealed the intracranial vessel dilatation, a cerebral blood flow increase, a flow velocity decrease, and cerebral venous thrombosis whereas some studies showed intracranial hypotension associated with vasoconstrictions and flow velocity increases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSF circulation can use as a compensatory mechanism in the brain for the clearance of CO2 (29). Based on the MKH hypothesis, there is a decrease in CSF during Intracranial hemorrhage because of the resulting increase in brain volume by increasing blood ow which can be considered an early quantitative biomarker of cerebral edema after ischemic stroke (30).…”
Section: Discussionmentioning
confidence: 99%
“…Dural tears are one etiology of intraoperative or postoperative cerebrospinal fluid leakage but are not the only mechanism. Intracranial hemorrhage is related to the velocity and volume of cerebrospinal fluid leakage ( 23 ). The mainstream hypotheses can be summarized as follows: (I) intracranial hemorrhage may be caused by brain tissue shift and vascular traction secondary to cerebrospinal fluid leakage-induced low intracranial pressure; (II) intracranial hemorrhage may be caused by vascular rupture as a result of excessive congestion of veins; (III) epidural hematoma is caused by the separation of the dura and skull inner plate as a result of spinal surgery-induced low intracranial pressure; and (IV) subdural hematoma is caused by subdural venous rupture as a result of low intracranial pressure following chronic cerebrospinal fluid leakage.…”
Section: Discussionmentioning
confidence: 99%